CCCTB 4 EU? SA vs. FA w/ FTA - Ronald B. Davies (University College Dublin, UCD School of Economics, 2012)
Since its conception, some within the European Union have expressed concerns over the ability of multinationals to avoid taxation by undertaking transfer pricing to shift profits towards low tax locations. These concerns have been growing, leading to a renewed call for a common consolidated corporate tax base wherein profits are allocated to nations according to a formula rather than firms' internal prices. This paper analyzes the merits of such a shift in taxation. In particular, it is shown that, given tax rates, implementing formula apportionment can result in greater tax revenues and less intense tax competition particularly for lower trade barriers. However, this is not always the case and depends on parameter values, including those describing the extent of economic integration.
Keywords: F24; F36; H25; H87; 330; Common Consolidated Tax Base; Vertical FDI; Formula Apportionment